Electrical characteristic of PVC-LiTFSI-Al₂0₃ (micro size) polymer electrolyes / Fadzil Abd Rashid - Abd Rashid, Fadzil (2008)
In this study of composite polymer electrolyte, poly (vinyl Chloride), (PVC) was used as the host polymer and lithium (bis) trifluoromethanesulfonimide, (LiTFSI) as the doping salt with Alumina, AI2O3 as the filler. PVC and salt in different wt% concentrations were dissolved in Tetrahydtofuran (THF). The influence of different concentrations of salt on PVC gave rise to different values of ionic conductivity. The best ionic conductivity was choosen for further experiment. The best ionic conductivity of PVC-LiTFSI was mixed with micro size of filler to form PVC-LiTFSI- AI2O3 composite polymer electrolyte. The ionic conductivity of the samples was determined by impedance spectroscopy. Temperature dependence of conductivity behavior of the best conducting PVC-LiTFSI and PVC-LiTFSI- AI2O3 samples were also investigated to obtain the values of activation energy (Ea) of conduction.